Fenestration of Axillary Vein by a Variant Axillary Artery - Hadimani, GA; Desai, SD; Bagoji, IB; Patil, BS (Kathmandu University Medical Journal, 2015)
Variations of venous pattern in the arm are common. In this case report, we present a variation of axillary artery and vein. During routine educational dissections of axillary region, it was observed that a fenestrated axillary vein was perforated by a variant axillary artery in right arm of an old male cadaver. The axillary artery which was fenestrated through axillary vein had only two branches arising from its second part and no branches from its remaining distal parts. The branches are thoraco-acromial (usual) and another large collateral (unusual) branch. This collateral branch is the origin of several important arteries as the subscapular, circumflex scapular, posterior circumflex humeral and lateral thoracic arteries. We propose to name this artery as collateral axillary arterial trunk. The course of this collateral axillary arterial trunk and its branches and also clinical significance of this variation are discussed in the paper. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12494 Kathmandu University Medical Journal Vol.11(2) 2013: 162-164